White blood count in patients on regular haemodialysis - Papadimitriou, M. (1969)
Total white cell, neutrophil, and lymphocyte counts were compared in patients with chronic renal failure treated successively by conservative means (low-protein diet), regular haemodialysis, and renal allotransplantation. The lowest total white cell and neutrophil counts and the highest lymphocyte counts were found in patients on regular haemodialysis. A rapid fall in neutrophil count during the first half-hour of dialysis and a more gradual fall between the first and sixth hours were observed. Adherence of neutrophils and mononuclear cells to the cuprophane (PT 150) dialysis membrane has been shown.